Development of Palm Shell Base Activated Carbon for Volatile Organic Compounds (VOCs) Emissions Absorption - Abdul Mutalib bin Leman; Muhammad Syafiq Muzarpar; Mohd Norhafsam Maghpor; Khairunnisa Rahman; Nik Normunira Mat Hassan; Nurasyikin Misdan; Supaat Zakaria (Institute for Research on Innovation and Industrial System (IRIS), 2021)
High concentration of indoor air contaminant commonly released by human activities, furniture, building materials, carpets, cleaning product and paints. BTEX contains Benzene, Toluene, Ethylbenzene and Xylene (BTEX) is categorized into VOCs which are indicative of harmful chemicals especially for indoor air. Therefore, it needs the sampling media for absorption before it could be analyse in the specific laboratory. One of the challenging technology to absorb BTEX is by using Palm Shell Activated Carbon (PSAC). Malaysia has a second largest country that produce palm oil which led to abundant of palm shell as waste material. Activated carbon is created through the carbonization, crushing and activation process. Carbonization process is conducted in various holding time of 1, 2 and 3 hours which called by CT1. CT2 and CT3 hours, respectively. Activation process is conducted through physical activation at temperature of 900 0C for 1 hour, chemical activation is conducted by Potassium Hydroxide (KOH) with ratio of 1:1 (charcoal: chemical) and holding time for 12 hours. It heated by furnace at temperature of 850 0C for 1 hours in order to improve the porosity and larger surface area. The physical properties were conducted by ASTM 3713, 3714 and 3715 for moisture, as and volatile content measurement. Surface morphology and composition as well as porosity image is characterized by Scanning Electron Microscopy (SEM) coupled by Energy Dispersive Spectroscopy (EDS) machine. The result shows that the lowest ash, moisture and volatile content is shown by CT1 sample, but it has not completely carbonized as compared to CT2 and CT3. Moreover, CT3 has highest ash, moisture and volatile content but it has lowest fixed carbon as compared to CT1 and CT2. Therefore, CT2 hours is selected for further process. In microstructure analysis is observed that the PSACphysical+chemical has larger number of porosities with the diameter approximately of 50 to 150 µm, for PSACphysical approximately of 25 to 100 µm and PSACchemical of below than 50 µm. Composition analysis is observed that the sample is mainly consists of Carbon (C), Oxygen (O) and Potassium (K) content. Where larger porosity is in-line with the increment of K content which indicated in larger adsorption capacity. It can be summarized that palm shell with 2 hours carbonization time and it activated become PSACphysical+chemical has a high potential to larger adsorption capacity of indoor air contaminant adsorption. It is being further explore for sampling media of BTEX.